Nature of selenium hydrogen bonding: gas phase spectroscopy and quantum chemistry calculations - Mishra, Kamal K.; Singh, Santosh K.; Ghosh, Paulami; Ghosh, Debashree; Das, Aloke (Physical chemistry Chemical physics, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Subsequent to the recent re-definition of hydrogen bonding by the IUPAC committee, there has been a growing search for finding the presence of this ever interesting non-covalent interaction between a hydrogen atom in an X-H group and any other atom in the periodic table. In recent gas phase experiments, it has been observed that hydrogen bonding interactions involving S and Se are of similar strength to those with an O atom. However, there is no clear explanation for the unusual strength of this interaction in the case of hydrogen bond acceptors which are not conventional electronegative atoms. In this work, we have explored the nature of Se hydrogen bonding by studying indole...dimethyl selenide (indmse) and phenol...dimethyl selenide (phdmse) complexes using gas phase IR spectroscopy and quantum chemistry calculations. We have found through various energy decomposition analysis (EDA) methods and natural bond orbital (NBO) calculations that, along with electrostatics and polarization, charge transfer interactions are important to understand Se/S hydrogen bonding and there is a delicate balance between the various interactions that plays the crucial role rather than a single component of the interaction energy. An in-depth understanding of this type of non-covalent interaction has immense significance in biology as amino acids containing S and Se are widely present in proteins and hence hydrogen bonding interactions involving S and Se atoms contribute to the folding of proteins.
Keywords: Center-Dot-O; Clusters; Co-Ordination; Complexes; intermolecular interactions; Proteins; Replacement; spectra; Strength; Sulfur

Interconverting hydrogen-bonding and weak n -> pi* interactions in aqueous solution: A direct spectroscopic evidence - Deb, Pranab; Jin, Geun Young; Singh, Santosh K.; Moon, Juran; Kwon, Hyejin; Das, Aloke; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry Letters, 2018)
Molecular structure and function depend on myriad noncovalent interactions. However, the weak and transient nature of noncovalent interactions in solution makes them challenging to study. Information on weak interactions is typically derived from theory and indirect structural data. Solvent fluctuations, not revealed by structure analysis, further complicate the study of these interactions. Using 2D infrared spectroscopy, we show that the strong hydrogen bond and the weak n -> pi* interaction coexist and interconvert in aqueous solution. We found that the kinetics of these interconverting interactions becomes faster with increasing water content. This experimental observation provides a new perspective on the existence of weak noncovalent interactions in aqueous solution.

Bis(silanetellurone) with C-H center dot center dot center dot Te Interaction - Ghosh, Moushakhi; Panwaria, Prakash; Tothadi, Srinu; Das, Aloke; Khan, Shabana (Inorganic Chemistry, 2020)
Herein, we report the synthesis of a series of bis(silanechalcogenones) [Ch = Te (2), S (3), or Se (4)] using an N-heterocyclic silylene-based SiCSi pincer ligand (1). 2 is the first example of a bis(silanetellurone) derivative. The bonding patterns of 2-4 were extensively studied by natural bond orbital, quantum theory of atoms in molecules, and noncovalent interaction index analyses, and these exhibit weak C-H center dot center dot center dot Ch interaction. The analogous reaction of 1 with trimethyl N-oxide produced a novel bis(cyclosiloxane) derivative (5). All of the complexes are duly characterized by single-crystal X-ray diffraction studies, multinuclear nuclear magnetic resonance (H-1, C-13, and Si-29) spectroscopy, and high-resolution mass spectrometry.